Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Keaktifan dan Hasil Belajar Siswa dalam Pelajaran Agama Katolik - Yustinus Sanda; Lorensius Amon (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2019)
This study tested the Jigsaw cooperative learning model on students and whether or not there was an increase in student activity and learning outcomes. Jigsaw cooperative learning is a learning model that focuses on expert group and home group discussions. The problem posed is the subject matter of Catholic Religion and Morals. This research is a classroom action research, consisting of two cycles focused on increasing student activity and learning outcomes. The results of this study indicate that the application of the Jigsaw-type cooperative learning model can effectively increase student activity and learning outcomes based on each indicator in the first and second cycles. The visual activity indicator has increased by 10%; oral activity indicator increased by 10%; the indicator of listening activity increased by 13.9%; the indicator of writing activity increased by 8.6%; indicators of mental activity increased by 17%, and indicators of emotional activity increased by 18.6%. Overall, the average score of an increase in the learning activity is 12.8% and learning outcomes are 1%.